What is currently known about the genetics of venous thromboembolism at the dawn of next generation sequencing technologies - Trégouët, David‐Alexandre; Morange, Pierre‐Emmanuel (British journal of haematology, 2018)
Summary Venous thromboembolism (VTE) has a strong genetic component. This review summarizes what is known at the seventeen genes that are now well established to harbour VTE‐associated genetic variants. In addition, it discusses additional candidate genes that deserve further validation before being claimed as VTE associated genes. Finally, several research strategies are briefly described to identify other molecular determinants of the disease.